Lithium ion battery
By using nanometal-reinforced aluminum-plastic film in lithium-ion batteries, the problem of insufficient heat dissipation at high voltages is solved, the battery's safety and thermal stability are improved, and the battery's fire or explosion risk is avoided due to overheating. .
Patent Information
- Application Number
- CN202411360428.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Soft-pack lithium-ion batteries have safety hazards under high voltages, especially after the silicon doping ratio increases sharply, which may lead to chemical reactions and battery cells ignite or explode, and the heat dissipation problem cannot be effectively solved, affecting them. Safety and stability.
Using an aluminum-plastic film containing nanometals, by adding nanometals of 35nm to 75nm particle size to the composite nylon layer, combining polypropylene film and aluminum foil, a strip-like convex structure is designed to improve heat dissipation performance and ensure the temperature of the diaphragm inside the battery cell. Conduct heat in time when rising and reduce the internal temperature of the battery cell.
It effectively improves the heat dissipation rate of the battery, reduces the sharp increase in the internal temperature of the battery cell, reduces the risk of fire or explosion caused by overheating, improves the safety and thermal stability of the battery, and extends the service life of the battery.
Smart Images

Figure CN119324279A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium ion battery. Background Art
[0002] Soft-pack lithium-ion batteries are widely used in various digital products and mobile devices due to their high energy density, low self-discharge rate, wide operating temperature range and environmental protection characteristics. With the continuous upgrading of electronic products, especially the development of portable mobile communication tools, these devices have evolved from the previous single text and voice communication to communication tools and entertainment devices that integrate multiple information and multimedia functions such as text, voice, image, video, etc. This change has greatly increased the functional complexity of electronic products and led to a significant increase in their power consumption.
[0003] In response to the demand for battery energy density, researchers are constantly exploring and applying new battery materials. Silicon has been widely studied as an additive component of negative electrode materials because of its high gram capacity. Silicon-doped negative electrodes are seen as one of the effective ways to increase battery energy density. However, with the increase in silicon doping ratio and operating voltage, the safety performance of batteries faces severe challenges. For example, under high voltage, negative electrode batteries containing 10% silicon carbon showed significant safety hazards in thermal abuse tests. The increase in external temperature will cause violent chemical reactions inside the battery cell, and the SEI film (solid electrolyte interface film) of the silicon negative electrode will quickly fail. The heat generated by the reaction between the exposed silicon negative electrode surface and the electrolyte cannot be effectively dissipated, resulting in a sharp rise in the temperature inside the battery cell. Ultimately, this heat accumulation may cause lithium cobalt oxide to decompose, which in turn causes the battery cell to catch fire or explode, which is more likely to occur than with traditional graphite negative electrode batteries.
[0004] Although soft-pack lithium batteries have made significant progress in energy density, their performance in thermal management is still unsatisfactory. Heat dissipation has become a key bottleneck restricting its further development, affecting the safety and stability of the battery. Therefore, improving the heat dissipation performance of soft-pack lithium batteries has become an important issue that needs to be solved urgently. Summary of the invention
[0005] The present invention aims to solve at least one of the above technical problems existing in the prior art. To this end, the present invention provides a lithium-ion battery that can transfer heat to the outside of the battery cell in a timely manner when the temperature inside the battery cell rises, so that the diaphragm is less heated inside the battery cell, thereby achieving the purpose of safety.
[0006] A first aspect of the present invention provides a lithium ion battery, comprising a battery cell and an aluminum-plastic film wrapping the battery cell, wherein the battery cell comprises a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, the separator has a shrinkage rate of Y%, the aluminum-plastic film comprises a polypropylene film, an aluminum foil and a composite nylon layer arranged in sequence, nano-metals are distributed in the composite nylon layer, the particle size of the nano-metals is 35nm to 75nm, and the amount of the nano-metals added to the composite nylon layer is Zwt%, and the relationship between Y and Z satisfies 0.18≤Y / Z≤1.45.
[0007] One of the technical solutions of the present invention regarding the aluminum-plastic film has at least the following beneficial effects:
[0008] When a high-voltage silicon-carbon negative electrode (10% SiC) lithium battery is subjected to thermal abuse during testing, the external temperature rise will cause a chemical reaction inside the battery cell, the silicon negative electrode SEI film will react rapidly, and the exposed silicon negative electrode surface will generate reaction heat with the electrolyte. The reaction heat accumulation cannot be released, which will cause the internal temperature of the battery cell to rise sharply, until the lithium cobalt oxide decomposes, the battery cell catches fire or explodes, and the test fails, which is more likely to fail than the traditional graphite negative electrode. To solve the rapid rise in temperature, the purpose can be achieved by increasing the heat dissipation on the surface of the battery cell and releasing the internal temperature of the battery cell. The shrinkage rate of the isolation film has a certain correlation with the coating amount of the isolation film coating. The smaller the shrinkage rate, the better the safety performance. It can ensure that the shrinkage rate of the isolation film in the TD direction (perpendicular to the length direction) above 130°C is small, avoiding the situation of short circuit between the positive and negative electrodes. However, for isolation films of the same thickness, the shrinkage rate is inversely proportional to the manufacturing cost of the isolation film. The smaller the shrinkage rate, the thicker the ceramic layer or the better the process parameters are required. The present invention uses an aluminum-plastic film containing nano-metals to match isolation films with higher shrinkage rates. Specifically, the aluminum-plastic film containing nano-metals of the present invention can be used in combination with a cheaper (larger shrinkage rate in TD direction at 130°C 0.5H), the shrinkage rate of the isolation membrane is Y%, the amount of nano-metal added to the composite nylon layer is Zwt%, and the relationship between Y and Z satisfies 0.18≤Y / Z≤1.45. When the temperature inside the battery cell rises, the heat can be promptly transferred to the outside of the battery cell, so that the separator is less heated inside the battery cell, thereby achieving the purpose of safety.
[0009] According to the simplified model of heat generation and heat dissipation balance during battery operation, Q-δ=mCp.m(dT / dt), where Q is the heat generation rate of the battery, δ is the heat dissipation rate, m is the mass, Cp.m is the specific heat capacity, T is the temperature, and t is the time. The greater the heat dissipation rate, the more balanced the entire equation is, and the less likely the object is to fail thermally and burn. This paper uses high thermal conductivity nanometal doped into the nylon layer to quickly export the reaction heat generated inside the battery cell when the temperature rises in the test hot box, thereby increasing the heat dissipation rate and improving the hot box pass rate of the silicon negative electrode.
[0010] According to some embodiments of the present invention, the shrinkage rate Y% of the isolation film ranges from 0.9% to 4.5%.
[0011] According to some embodiments of the present invention, the shrinkage rate Y% of the isolation film can range from 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, any one of the values or a range formed by any two of them, such as 2.0% to 4.0%.
[0012] According to some embodiments of the present invention, the addition amount Zwt% of the nano-metal in the composite nylon layer ranges from 1% to 5%.
[0013] According to some embodiments of the present invention, the amount Zwt% of the nano-metal added to the composite nylon layer may range from 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%. , 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, any value or a range formed by any two of them, for example 3.0% to 5.0%.
[0014] According to some embodiments of the present invention, the isolation film includes a base layer and a surface layer which are sequentially arranged.
[0015] According to some embodiments of the present invention, the material of the base layer includes PP or PE.
[0016] According to some embodiments of the present invention, the material of the surface layer includes PVDF and alumina ceramics.
[0017] According to some embodiments of the present invention, a plurality of strip-shaped protrusions are provided on the outer surface of the composite nylon layer.
[0018] The strip-shaped protrusions can further expand the heat dissipation area.
[0019] According to some embodiments of the present invention, the line width of the strip-shaped protrusions is 0.1 mm to 0.3 mm.
[0020] According to some embodiments of the present invention, the height of the strip-shaped protrusions is 4 micrometers to 8 micrometers.
[0021] According to some embodiments of the present invention, the height of the strip-shaped protrusions is any one of 4 micrometers, 5 micrometers, 6 micrometers, 7 micrometers, and 8 micrometers, or a range formed by any two of them.
[0022] According to some embodiments of the present invention, the strip-shaped protrusions are parallel to each other.
[0023] According to some embodiments of the present invention, the spacing between the strip-shaped protrusions is 0.5 mm to 2 mm.
[0024] According to some embodiments of the present invention, the spacing between the strip-shaped protrusions is any one value among 0.5 mm, 1.0 mm, 1.5 mm, 2.0 mm, or a range formed by any two of them.
[0025] According to some embodiments of the present invention, the strip-shaped protrusions are in a sinusoidal waveform.
[0026] According to some embodiments of the present invention, the cross-section of the strip-shaped protrusion includes at least one of an arch, a triangle and a rectangle.
[0027] According to some embodiments of the present invention, the polypropylene film has a thickness of 30 micrometers to 80 micrometers.
[0028] According to some embodiments of the present invention, the thickness of the polypropylene film is any value of 30 micrometers, 40 micrometers, 50 micrometers, 60 micrometers, 70 micrometers, 80 micrometers, or a range formed by any two of them.
[0029] According to some embodiments of the present invention, the thickness of the aluminum foil is 20 micrometers to 40 micrometers.
[0030] According to some embodiments of the present invention, the thickness of the aluminum foil is any one of 20 micrometers, 25 micrometers, 30 micrometers, 35 micrometers, 40 micrometers, or a range formed by any two of them.
[0031] According to some embodiments of the present invention, the composite nylon layer has a thickness of 20 micrometers to 40 micrometers.
[0032] According to some embodiments of the present invention, the thickness of the composite nylon layer is any one of 20 micrometers, 25 micrometers, 30 micrometers, 35 micrometers, 40 micrometers, or a range formed by any two of them.
[0033] According to some embodiments of the present invention, a polyurethane adhesive layer is provided between the polypropylene film and the aluminum foil.
[0034] According to some embodiments of the present invention, the thickness of the polyurethane adhesive layer is 1 micrometer to 3 micrometers.
[0035] According to some embodiments of the present invention, the thickness of the polyurethane adhesive layer is any value of 1 micrometer, 1.5 micrometers, 2 micrometers, 2.5 micrometers, 3 micrometers, or a range formed by any two of them.
[0036] According to some embodiments of the present invention, a polyethylene naphthalate adhesive layer is provided between the aluminum foil and the composite nylon layer.
[0037] According to some embodiments of the present invention, the polyethylene naphthalate adhesive layer has a thickness of 1 micrometer to 3 micrometers.
[0038] According to some embodiments of the present invention, the thickness of the polyethylene naphthalate adhesive layer is any value of 1 micrometer, 1.5 micrometers, 2 micrometers, 2.5 micrometers, 3 micrometers, or a range formed by any two of them.
[0039] According to some embodiments of the present invention, the nanometal includes nanosilver or nanocopper.
[0040] The thermal conductivity of silver is 429W / (m·K), the thermal conductivity of copper is generally 385W / (m·K), and the thermal conductivity of aluminum is 237W / (m·K). The thermal conductivity of the adhesive layer is generally less than 1W / (m·K).
[0041] According to some embodiments of the present invention, the morphology of the nanometal includes nanosheets or nanoparticles.
[0042] According to some embodiments of the present invention, the method for preparing the aluminum-plastic film includes the steps of co-molding the nano-metal and nylon particles to obtain a composite nylon layer, and then compounding the polypropylene film, aluminum foil and the composite nylon layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 It is a cross-sectional structural diagram of the aluminum-plastic film of Example 1.
[0044] Figure 2 It is a top view of the aluminum-plastic film with a sine-wave protrusion.
[0045] Figure 3 It is a top view of the aluminum-plastic film with protrusions as parallel lines. DETAILED DESCRIPTION
[0046] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.
[0047] In the first aspect, in some embodiments of the present invention, the first aspect of the present invention provides a lithium-ion battery, comprising a battery cell and an aluminum-plastic film wrapping the battery cell, the battery cell comprising a positive electrode plate, a separator, a negative electrode plate and an electrolyte, the shrinkage rate of the separator is Y%, the aluminum-plastic film comprises a polypropylene film, an aluminum foil and a composite nylon layer arranged in sequence, nano-metals are distributed in the composite nylon layer, the particle size of the nano-metals is 35nm to 75nm, and the amount of the nano-metals added to the composite nylon layer is Zwt%, and the relationship between Y and Z satisfies 0.18≤Y / Z≤1.45.
[0048] It can be understood that when a high-voltage silicon-carbon negative electrode (10% SiC) lithium battery is subjected to thermal abuse during testing, external temperature rise will cause a chemical reaction inside the battery cell, the silicon negative electrode SEI film will react rapidly, and the exposed silicon negative electrode surface will generate reaction heat with the electrolyte. The reaction heat accumulation cannot be released, which will cause the internal temperature of the battery cell to rise sharply, until the lithium cobalt oxide decomposes, the battery cell catches fire or explodes, and the test fails, which is more likely to fail than the traditional graphite negative electrode. To solve the rapid rise in temperature, the purpose can be achieved by increasing the heat dissipation on the surface of the battery cell and releasing the internal temperature of the battery cell. The shrinkage rate of the isolation film has a certain correlation with the coating amount of the isolation film coating. The smaller the shrinkage rate, the better the safety performance. It can ensure that the shrinkage rate of the isolation film in the TD direction (perpendicular to the length direction) above 130°C is small, avoiding the situation of short circuit between the positive and negative electrodes. However, for isolation films of the same thickness, the shrinkage rate is inversely proportional to the manufacturing cost of the isolation film. The smaller the shrinkage rate, the thicker the ceramic layer or the better the process parameters are required. The present invention uses an aluminum-plastic film containing nano-metals to match isolation films with higher shrinkage rates. Specifically, the aluminum-plastic film containing nano-metals of the present invention can be used in combination with a cheaper (larger shrinkage rate in TD direction at 130°C 0.5H), the shrinkage rate of the isolation membrane is Y%, the amount of nano-metal added to the composite nylon layer is Zwt%, and the relationship between Y and Z satisfies 0.18≤Y / Z≤1.45. When the temperature inside the battery cell rises, the heat can be promptly transferred to the outside of the battery cell, so that the separator is less heated inside the battery cell, thereby achieving the purpose of safety.
[0049] According to the simplified model of heat generation and heat dissipation balance during battery operation, Q-δ=mCp.m(dT / dt), where Q is the heat generation rate of the battery, δ is the heat dissipation rate, m is the mass, Cp.m is the specific heat capacity, T is the temperature, and t is the time. The greater the heat dissipation rate, the more balanced the entire equation is, and the less likely the object is to fail thermally and burn. This paper uses high thermal conductivity nanometal doped into the nylon layer to quickly export the reaction heat generated inside the battery cell when the temperature rises in the test hot box, thereby increasing the heat dissipation rate and improving the hot box pass rate of the silicon negative electrode.
[0050] In combination with the first aspect, in some embodiments of the present invention, the shrinkage rate Y% of the isolation film ranges from 0.9% to 4.5%.
[0051] In combination with the first aspect, in some embodiments of the present invention, the shrinkage rate Y% of the isolation film can range from 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, any one of the values or any two of the range values formed, such as 2.0% to 4.0%.
[0052] In combination with the first aspect, in some embodiments of the present invention, the addition amount Zwt% of the nano-metal in the composite nylon layer is in the range of 1% to 5%.
[0053] In combination with the first aspect, in some embodiments of the present invention, the addition amount Zwt% of the nanometal in the composite nylon layer can range from 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8 %, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, any value or a range formed by any two of them, for example 3.0% to 5.0%.
[0054] In combination with the first aspect, in some embodiments of the present invention, the isolation film includes a base layer and a surface layer which are arranged in sequence.
[0055] In combination with the first aspect, in some embodiments of the present invention, the material of the base layer includes PP or PE.
[0056] In combination with the first aspect, in some embodiments of the present invention, the material of the surface layer includes PVDF and alumina ceramics.
[0057] In combination with the first aspect, in some embodiments of the present invention, a plurality of strip-shaped protrusions are provided on the outer surface of the composite nylon layer.
[0058] In combination with the first aspect, in some embodiments of the present invention, the cross-section of the strip-shaped protrusion includes at least one of an arch, a triangle, and a rectangle.
[0059] The strip-shaped protrusions can further expand the heat dissipation area.
[0060] In combination with the first aspect, in some embodiments of the present invention, the line width of the strip-shaped protrusion is 0.1 mm to 0.3 mm.
[0061] The design of the strip-shaped protrusions increases the effective heat dissipation area of the film surface and enhances the heat dissipation capacity, thereby improving the heat dissipation efficiency of the entire battery cell. The shape of this protrusion helps to evenly distribute the heat generated on the surface of the battery cell and prevents heat from accumulating in local areas, thereby reducing the risk of overheating. The strip-shaped protrusions can increase the contact area between the aluminum-plastic film and the battery cell, improve thermal conductivity, and ensure more efficient heat conduction. These strip-shaped protrusions can also enhance the structural strength of the film, making it less likely to deform or fail in high temperature environments, and improving the overall reliability of the film. By increasing the heat dissipation channel, these strip-shaped protrusions help accelerate the release of heat inside the battery cell, reduce the temperature rise rate of the battery in thermal abuse testing, and improve the safety and thermal stability of the battery.
[0062] In combination with the first aspect, in some embodiments of the present invention, the height of the strip-shaped protrusions is 4 micrometers to 8 micrometers.
[0063] The strip-shaped protrusions can help disperse and evenly distribute heat, reduce local heat accumulation, improve the overall heat dissipation effect, and reduce the temperature rise rate inside the battery. By increasing the microscopic roughness of the membrane surface, the strip-shaped protrusions can promote the conduction of heat on the membrane surface and improve the efficiency of transferring heat from the inside of the battery cell to the outside. The strip-shaped protrusions can form a tiny air layer between the contact surface of the membrane and the outside world. Although this air layer is thin, it helps to improve the heat exchange performance of the membrane and effectively assists in the discharge of heat from the inside of the battery cell. These protrusions provide a certain structural support on the surface of the membrane, enhance the overall stability of the membrane, and make it less likely to deform or fail in a high temperature environment. In the thermal abuse test of high-voltage silicon-carbon negative electrode lithium batteries, this high strip-shaped protrusion helps to release the reaction heat generated inside to the outside faster, improve the battery's hot box pass rate, and reduce the risk of fire or explosion caused by overheating.
[0064] In combination with the first aspect, in some embodiments of the present invention, the height of the strip-shaped protrusion is any value of 4 micrometers, 5 micrometers, 6 micrometers, 7 micrometers, 8 micrometers, or a range formed by any two of them.
[0065] In combination with the first aspect, in some embodiments of the present invention, the strip-shaped protrusions are parallel to each other.
[0066] The parallel strip protrusions can create a regular heat dissipation surface, which helps to evenly distribute the heat on the battery surface, avoid local overheating, and improve the overall heat dissipation efficiency. The parallel strip protrusions can effectively form multiple heat conduction channels, so that heat can be conducted to the surface of the membrane faster along these channels, promoting the rapid release of heat. This design can reduce the thermal resistance caused by uneven surface or irregular structure, and ensure that heat can be guided and dissipated through a more intuitive path. The arrangement of parallel strip protrusions optimizes the effective heat dissipation area of the membrane. Compared with other irregular structures, the parallel arrangement helps to increase the contact area between the membrane and the surrounding air, thereby improving the heat dissipation efficiency. The parallel strip protrusions can also increase the overall mechanical stability of the membrane, making the membrane less likely to deform or damage under high temperature and thermal shock, ensuring long-term stable performance. The parallel design of the strip protrusions forms an orderly heat exchange structure on the membrane surface, which helps to optimize the conduction and convection of heat and improve the heat exchange effect. As a result, the parallel strip protrusions make the aluminum-plastic film more efficient in heat dissipation and thermal management, and can better cope with the thermal abuse of high-voltage silicon-carbon negative electrode lithium batteries, thereby improving the safety and performance of the batteries.
[0067] In combination with the first aspect, in some embodiments of the present invention, the spacing between the strip-shaped protrusions is 0.5 mm to 2 mm.
[0068] In combination with the first aspect, in some embodiments of the present invention, the spacing between the strip-shaped protrusions is any value of 0.5 mm, 1.0 mm, 1.5 mm, 2.0 mm, or a range formed by any two of them.
[0069] In combination with the first aspect, in some embodiments of the present invention, the strip-shaped protrusions are in a sinusoidal waveform.
[0070] The raised structure of the sinusoidal waveform can effectively increase the contact area. Compared with a straight line or a plane, the waveform structure provides more heat dissipation surfaces, which helps to improve the efficiency of heat dissipation. The sinusoidal waveform can also make the heat flow more evenly distributed on the membrane surface, reduce the phenomenon of local heat concentration, help prevent the formation of hot spots, and improve the overall heat dissipation effect. In addition, the waveform design promotes natural convection of air flow and increases the speed of heat exchange, which helps to take away the heat from the membrane surface more quickly. The sinusoidal waveform structure can improve the overall mechanical stability of the membrane, prevent deformation or rupture caused by temperature changes, and improve the durability of the membrane. The waveform design also reduces the conduction resistance of heat in the membrane, allowing heat to be released more effectively through the membrane surface, thereby improving the heat dissipation efficiency. The raised structure of the sinusoidal waveform helps to evenly dissipate heat, is not easy to form hot spots, and ensures the consistency of the overall heat dissipation effect of the membrane surface.
[0071] In combination with the first aspect, in some embodiments of the present invention, the thickness of the polypropylene film is 30 micrometers to 80 micrometers.
[0072] First, the appropriate thickness can provide sufficient mechanical strength and tear resistance, ensuring that the aluminum-plastic film remains stable in practical applications and is not easy to break or fail. Secondly, the appropriate thickness helps to improve the barrier properties to water vapor and gas, protect the internal materials of the battery from the influence of the external environment, and extend the service life of the battery. Third, the polypropylene film has good thermal stability, and the moderate thickness can effectively withstand thermal stress and reduce deformation or degradation under high temperature conditions, thereby ensuring the stable performance of the aluminum-plastic film. Fourth, the appropriate thickness helps to achieve uniform material distribution during co-molding or other molding processes, ensuring the structural consistency and performance reliability of the final product. Therefore, choosing a polypropylene film thickness of 30 microns to 80 microns can bring comprehensive advantages in enhancing material strength, barrier properties, thermal stability and processing performance, thereby improving the overall application effect of the aluminum-plastic film in lithium batteries.
[0073] In combination with the first aspect, in some embodiments of the present invention, the thickness of the polypropylene film is any value of 30 micrometers, 40 micrometers, 50 micrometers, 60 micrometers, 70 micrometers, 80 micrometers, or a range formed by any two of them.
[0074] In combination with the first aspect, in some embodiments of the present invention, the thickness of the aluminum foil is 20 micrometers to 40 micrometers.
[0075] As a key layer in aluminum-plastic film, one of the main functions of aluminum foil is to provide excellent gas and water vapor isolation performance. The thickness of 20 microns to 40 microns ensures that the aluminum foil can effectively isolate external moisture and gas, thereby protecting the chemical substances and electrolytes inside the battery and extending the service life of the battery. Aluminum foil in this thickness range performs well in maintaining sufficient mechanical strength. It can resist external physical pressure, collision or extrusion, thereby maintaining the overall structural stability of the battery shell and preventing deformation or rupture during transportation and use. In addition, aluminum foil has good thermal conductivity. The thickness of 20 microns to 40 microns can provide appropriate thermal conductivity, so that the battery can more effectively conduct the generated heat away under high temperature conditions. Although the thermal conductivity of aluminum foil is not as outstanding as that of nano metal, within the thickness range, it can help regulate the internal temperature of the battery and avoid overheating problems. In battery applications, aluminum foil also has the function of electromagnetic shielding. The moderate thickness ensures that the aluminum foil can effectively shield external electromagnetic interference, protect the internal circuit of the battery from interference, and improve the working stability and reliability of the battery. The thickness of aluminum foil from 20 microns to 40 microns provides a good balance between production cost and performance. Too thick aluminum foil may lead to higher costs, while too thin aluminum foil may not provide adequate protection. Therefore, this thickness range can ensure that the various performance requirements of the aluminum-plastic film are met while controlling costs. Aluminum foil in this thickness range has good processability and can be well compounded with polypropylene film and composite nylon layer. It can ensure the overall structural consistency of the aluminum-plastic film during the co-molding process and ensure the quality and performance of the final product. Therefore, choosing an aluminum foil thickness of 20 microns to 40 microns can provide optimized effects in terms of isolation performance, mechanical strength, thermal conductivity, electromagnetic shielding and cost-effectiveness, thereby improving the comprehensive application performance of aluminum-plastic film in lithium batteries.
[0076] In combination with the first aspect, in some embodiments of the present invention, the thickness of the aluminum foil is any value of 20 micrometers, 25 micrometers, 30 micrometers, 35 micrometers, 40 micrometers, or a range formed by any two of them.
[0077] In combination with the first aspect, in some embodiments of the present invention, the thickness of the composite nylon layer is 20 micrometers to 40 micrometers.
[0078] Within this thickness range, the composite nylon layer can effectively combine with the structure doped with nanometal to improve the overall thermal conductivity. Although nylon itself has a low thermal conductivity, by designing within this thickness range, it can be ensured that the nanometal effectively improves the thermal conductivity of the material and helps to quickly remove the heat generated inside the battery cell. Specifically, a thickness of 20 microns to 40 microns can provide sufficient mechanical strength and durability so that the composite nylon layer is not easily deformed or damaged during battery operation. This strength is particularly important for protecting internal battery components and preventing damage caused by mechanical stress. Moderate thickness also helps the composite nylon layer maintain stability in high temperature environments and prevents performance degradation caused by thermal expansion or contraction. This can effectively improve the thermal stability of the aluminum-plastic film under extreme working conditions. The thickness of the composite nylon layer between 20 microns and 40 microns can provide moderate flexibility, allowing it to better adapt to different shapes and sizes during battery packaging and application, while maintaining good composite properties. The composite nylon layer in this thickness range can effectively balance the conduction and heat dissipation of heat and enhance the thermal management capabilities of the entire battery system. Through the appropriate thickness, the heat dissipation efficiency can be improved while ensuring thermal conductivity, thereby delaying the sharp increase in the temperature inside the battery. Selecting a thickness of 20 microns to 40 microns can achieve a good balance between performance and cost. Thicker composite nylon layers may bring additional costs, while thinner layers may not provide sufficient protection and thermal conductivity. This thickness range ensures high efficiency while controlling production costs. Composite nylon layers of this thickness can better adapt to various molding processes and composite material processing requirements during the manufacturing process, ensuring the quality and consistency of the final product. As a result, the composite nylon layer thickness of 20 microns to 40 microns can bring comprehensive advantages in optimizing thermal conductivity, enhancing mechanical strength, maintaining thermal stability, providing flexibility, improving thermal management, controlling costs, and improving processing adaptability, thereby improving the application effect of aluminum-plastic film in lithium batteries.
[0079] In combination with the first aspect, in some embodiments of the present invention, the thickness of the composite nylon layer is any value of 20 microns, 25 microns, 30 microns, 35 microns, 40 microns, or a range formed by any two of them.
[0080] In combination with the first aspect, in some embodiments of the present invention, a polyurethane adhesive layer is provided between the polypropylene film and the aluminum foil.
[0081] As an excellent bonding material, polyurethane can provide a strong bonding effect, firmly combining the polypropylene film and the aluminum foil. This strong bonding can prevent the aluminum foil from peeling off during use, ensuring the overall structural stability and durability of the aluminum-plastic film.
[0082] In addition, the polyurethane adhesive layer has excellent sealing properties, which helps prevent water vapor and gas penetration and enhances the barrier properties of the film layer. This is crucial for protecting the chemicals and electrolytes inside the lithium battery, avoiding the impact of environmental factors on battery performance. Polyurethane has good tolerance to a variety of chemicals and can resist the erosion of electrolytes and other chemicals, thereby extending the service life of the aluminum-plastic film and ensuring its long-term stability in the battery. The polyurethane adhesive layer provides additional flexibility, making the entire aluminum-plastic film more adaptable during use. It can effectively absorb and disperse stress and reduce damage caused by external shock or vibration. Polyurethane has good thermal stability and can maintain its bonding performance and structural stability in high temperature environments. This is especially important for the high temperature conditions of lithium batteries in thermal abuse tests, ensuring that the film layer can still work effectively under extreme conditions. The use of polyurethane adhesive layers can simplify the production process and make the composite process of polypropylene film and aluminum foil more efficient. The bonding properties of polyurethane can achieve high bonding quality in conventional production processes, thereby improving production efficiency and product consistency. Through the design of the polyurethane adhesive layer, the overall durability of the aluminum-plastic film is significantly improved. It can resist long-term mechanical stress and environmental factors, reduce aging and degradation of the film layer, and thus extend the service life of the product.
[0083] In terms of thermal management, the polyurethane adhesive layer can effectively relieve the stress caused by thermal expansion and contraction, help maintain the structural integrity of the film layer, and assist in improving the heat dissipation performance of the battery, especially in high-temperature testing. As a result, the use of the polyurethane adhesive layer between the polypropylene film and the aluminum foil provides enhanced bonding strength, improved sealing performance, excellent chemical resistance and thermal stability, and improves the flexibility, durability and production process efficiency of the film layer. These advantages enable the aluminum-plastic film to better protect the internal materials and improve the overall performance in lithium battery applications.
[0084] In combination with the first aspect, in some embodiments of the present invention, the thickness of the polyurethane adhesive layer is 1 micrometer to 3 micrometers.
[0085] The polyurethane adhesive layer can provide effective bonding strength in a thickness range of 1 micron to 3 microns. This thin layer can ensure a strong bond between the polypropylene film and the aluminum foil, thereby preventing peeling or delamination problems caused by mechanical stress or temperature changes during the use of the battery. It can reduce the space occupied inside the battery while maintaining high bonding strength. The polyurethane layer with a thickness of 1 micron to 3 microns can also provide excellent sealing performance to prevent the penetration of water vapor, gas and other external substances that may affect the performance of the battery. This thin layer can effectively protect the chemicals and electrolytes inside the battery, avoid the negative impact of the external environment on the battery, and improve the overall durability and stability of the battery. The thin layer of polyurethane adhesive layer has good thermal stability and can maintain stable bonding performance within the operating temperature range without significantly affecting the thermal conductivity of the film layer. In this way, it can effectively assist the battery in thermal management under high temperature or high heat load conditions without negatively affecting the heat dissipation performance of the battery. It can be understood that a thinner polyurethane adhesive layer can reduce the use of raw materials, thereby reducing production costs. Due to its thin thickness, the production and processing costs of this adhesive layer are low, and it can improve economic benefits while maintaining performance. The thin thickness of the polyurethane adhesive layer can provide a certain degree of flexibility, making the film more adaptable during the application process. This flexibility helps the aluminum-plastic film to better adapt to the needs of batteries of different shapes and sizes during the production and use of the battery, and reduce damage caused by mechanical stress. The thin layer of polyurethane adhesive layer can improve processing efficiency during the manufacturing process. Thinner layers can be more easily evenly coated and dried, thereby speeding up production and improving the overall efficiency of the production line. Further, the thickness of the polyurethane adhesive layer is between 1 micron and 3 microns, which can improve the bonding performance and protection ability of the overall film without significantly increasing the thickness of the film layer. This configuration ensures the comprehensive performance of the aluminum-plastic film in practical applications, including mechanical strength, sealing and thermal stability. The thin layer of polyurethane adhesive layer helps to improve the uniformity of the aluminum-plastic film. It can avoid the uneven thickness problem that may be caused by thicker layers, thereby ensuring the overall consistency and stability of the film layer, thereby improving the quality and reliability of the product. The thinner polyurethane adhesive layer can maintain the flexibility of the film layer and adapt to different application requirements. During the battery packaging process, it can better adapt to various shapes and sizes, ensuring that the film layer can tightly wrap the battery.
[0086] Therefore, a polyurethane adhesive layer with a thickness of 1 to 3 microns can bring beneficial effects in terms of bonding performance, sealing, thermal management, production cost, flexibility, processing efficiency and uniformity of the film layer, thereby improving the overall performance and economic benefits of the aluminum-plastic film in lithium battery applications.
[0087] In combination with the first aspect, in some embodiments of the present invention, the thickness of the polyurethane adhesive layer is any value of 1 micron, 1.5 microns, 2 microns, 2.5 microns, 3 microns, or a range formed by any two of them.
[0088] In combination with the first aspect, in some embodiments of the present invention, a polyethylene naphthalate adhesive layer is provided between the aluminum foil and the composite nylon layer.
[0089] The polyethylene naphthalate adhesive layer can provide strong and lasting bonding strength to ensure a firm bond between the aluminum foil and the composite nylon layer. This high-strength bond helps to improve the overall structural stability of the film layer and prevent delamination or peeling caused by mechanical stress or long-term use. In addition, the polyethylene naphthalate adhesive layer has good thermal stability and can maintain its performance unchanged in a high temperature environment. As an adhesive layer, it can withstand the thermal load of the battery under high temperature working conditions and is not easy to degrade or lose its bonding properties, thereby maintaining an effective bond between the aluminum foil and the composite nylon layer.
[0090] The polyethylene naphthalate adhesive layer also has excellent air tightness and moisture resistance, which can effectively prevent the penetration of water vapor and gas, and protect the chemical substances inside the battery from the influence of the external environment. This air tightness helps to extend the service life of the battery and improve its overall performance and stability. The high toughness and flexibility of the polyethylene naphthalate adhesive layer enable it to adapt to the expansion and contraction of the film layer, especially during the thermal expansion and cooling process of the battery. The flexible polyethylene naphthalate adhesive layer can reduce the mechanical stress caused by temperature changes, thereby improving the durability and reliability of the film layer. The polyethylene naphthalate adhesive layer is easy to process and coat, and can maintain uniform thickness and consistent performance during the film manufacturing process. This excellent processing performance allows the polyethylene naphthalate adhesive layer to be produced with stable quality and improve production efficiency. When the aluminum foil layer is combined with the polyethylene naphthalate adhesive layer, the electromagnetic shielding capability of the film layer can be further enhanced. The polyethylene naphthalate adhesive layer helps improve the shielding effect of the aluminum foil and prevents the influence of external electromagnetic interference on the internal electronic components of the battery. The addition of the polyethylene naphthalate adhesive layer can optimize the overall performance of the aluminum-plastic film, combining the excellent thermal conductivity of the aluminum foil with the mechanical strength and heat dissipation capacity of the composite nylon layer, thereby improving the use effect of the entire film layer in lithium batteries. Overall, the polyethylene naphthalate adhesive layer can provide excellent bonding strength, thermal stability, air tightness, flexibility and processing performance between the aluminum foil and the composite nylon layer, while enhancing the electromagnetic shielding ability and chemical resistance, thereby significantly improving the overall performance and reliability of the aluminum-plastic film in lithium batteries.
[0091] In combination with the first aspect, in some embodiments of the present invention, the thickness of the polyethylene naphthalate adhesive layer is 1 micrometer to 3 micrometers.
[0092] In combination with the first aspect, in some embodiments of the present invention, the thickness of the polyethylene naphthalate adhesive layer is any value of 1 micron, 1.5 microns, 2 microns, 2.5 microns, 3 microns, or a range formed by any two of them.
[0093] In combination with the first aspect, in some embodiments of the present invention, the nanometal includes nanosilver or nanocopper.
[0094] Both nanosilver and nanocopper have excellent thermal conductivity. Adding these nanometals to the composite nylon layer can significantly improve the thermal conductivity of the layer. The thermal conductivity of nanosilver is as high as about 429W / (m·K), while nanocopper is about 385W / (m·K), which greatly improves the overall thermal conductivity of the aluminum-plastic film, thereby more effectively conducting the heat generated inside the battery cell to the surface of the film layer. In addition, by improving the thermal conductivity of the composite nylon layer, nanometals can enhance the heat dissipation performance of the film layer. When chemical heat is generated inside the battery due to high temperature, nanometals help to accelerate the conduction and dispersion of heat, avoid heat concentration, and reduce the risk of failure of the battery cell due to overheating. Further, the addition of nanometals helps to reduce the risk of thermal failure of the battery cell due to increased temperature. By increasing the heat dissipation rate, the temperature increase of the battery cell can be more effectively controlled to avoid material decomposition, fire or explosion due to high temperature. It can be understood that the distribution of nanometals not only improves thermal conductivity, but may also have a positive impact on the structural stability of the composite nylon layer. Evenly distributed nanometals can enhance the mechanical strength of the film layer, improve its stability in high-temperature environments, and prevent interlayer separation or peeling.
[0095] Improving thermal conductivity and heat dissipation can significantly improve the performance of the battery in the thermal shock test, that is, improve the pass rate of the hot box. This is particularly important for high-voltage silicon-carbon negative electrode lithium batteries, because their stability in high temperature environments is crucial to safety. The use of high thermal conductivity nanometals helps to optimize the overall performance of the battery and extend the battery life. Better heat dissipation can ensure the stability of the battery during long-term use and reduce performance degradation caused by overheating. The high thermal conductivity of nanosilver and nanocopper can reduce the overall thermal management requirements of the film layer, so that the adaptability and efficiency of the aluminum-plastic film in the battery manufacturing process are improved, thereby improving production efficiency and product quality. By optimizing the heat conduction path and improving the heat dissipation efficiency, nanometals can effectively reduce the thermal failure problem caused by local overheating, thereby improving the safety and reliability of the battery. Therefore, introducing nanosilver or nanocopper into the composite nylon layer can significantly improve the thermal conductivity and heat dissipation of the aluminum-plastic film, reduce the risk of battery failure due to high temperature, optimize the overall performance of the battery, and improve the performance in the thermal shock test.
[0096] The thermal conductivity of silver is 429W / (m·K), the thermal conductivity of copper is generally 385W / (m·K), and the thermal conductivity of aluminum is 237W / (m·K).
[0097] The thermal conductivity of the adhesive layer is generally less than 1 W / (m·K).
[0098] In combination with the first aspect, in some embodiments of the present invention, the morphology of the nanometal includes nanosheets or nanoparticles.
[0099] Nano-sheet metal materials have a large specific surface area and can provide more heat conduction channels. Due to their flat shape, they are conducive to forming a continuous heat conduction network in the composite nylon layer, thereby effectively improving the overall thermal conductivity.
[0100] Nanosheets have strong thermal conductivity and can quickly conduct heat to reduce local high temperature phenomena. They can improve the uniform distribution of heat in the membrane and prevent overheating caused by heat concentration. By improving the thermal conductivity of the membrane layer, nanosheets can effectively reduce the rapid rise in temperature inside the battery. This can enhance the thermal stability of the membrane and reduce the risk of battery failure caused by high temperature. The increase in nanosheets can form a larger effective thermal conductivity area, allowing heat to be more effectively conducted from the inside of the battery cell to the outside, enhancing the heat dissipation efficiency. Due to their excellent thermal conductivity, nanosheets can significantly improve the performance of the battery cell in thermal shock tests and reduce failures caused by overheating. Due to their flat structure, nanosheets can effectively enhance the structural stability of the composite nylon layer and reduce material degradation or delamination in high temperature environments.
[0101] Although the thermal conductivity of a single particle may not be as good as that of a nanosheet, the dispersion of particles can enhance the thermal conductivity of the composite layer by providing multiple thermal conduction paths. Particles can effectively fill the gaps in the composite nylon layer and reduce thermal resistance. Nanoparticles can effectively improve thermal diffusivity by forming a complex thermal conduction network in the composite nylon layer, thereby helping to conduct heat to the outside of the membrane faster. The nanoparticles dispersed in the composite nylon layer not only improve thermal conductivity, but also increase the mechanical strength of the film layer, making the film layer less likely to deform or fail at high temperatures. Although the surface area of a single particle is small, through high-density distribution, they can improve the heat dissipation capacity of the entire film layer and effectively expand the heat dissipation area. The uniform distribution of particles can effectively enhance the thermal management ability of the film layer, making the thermal shock response of the battery cell in the test more stable and improving the pass rate of the hot box. The nanoparticles distributed in the composite nylon layer can improve the overall structural strength of the film layer and enhance its tolerance under extreme temperature conditions.
[0102] Whether it is nanosheets or nanoparticles, by optimizing thermal conductivity and structural stability, the overall performance of the battery can be improved, including improving battery safety, extending service life, and reducing performance degradation caused by high temperature.
[0103] In combination with the first aspect, in some embodiments of the present invention, the method for preparing the aluminum-plastic film includes the steps of co-molding nano-metal and nylon particles to obtain a composite nylon layer, and then compounding the polypropylene film, aluminum foil and the composite nylon layer.
[0104] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0105] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0106] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.
[0107] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.
[0108] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0109] Example 1
[0110] First, an aluminum-plastic film was prepared, and the structure was referenced Figure 1 Specifically, a polypropylene film 100, an aluminum foil 300 and a composite nylon layer 500 are arranged in sequence, nano-metal 510 is distributed in the composite nylon layer 500, and a plurality of strip-shaped protrusions are arranged on the outer surface of the composite nylon layer 500.
[0111] The thickness of the polypropylene film 100 is 55 micrometers.
[0112] The thickness of the aluminum foil 300 is 30 micrometers.
[0113] The thickness of the composite nylon layer 500 is 30 microns.
[0114] A polyurethane adhesive layer 200 is provided between the polypropylene film 100 and the aluminum foil 300 , and the thickness of the polyurethane adhesive layer 200 is 2 microns.
[0115] A polyethylene naphthalate adhesive layer 400 is provided between the aluminum foil 300 and the composite nylon layer 500 , and the thickness of the polyethylene naphthalate adhesive layer 400 is 2 microns.
[0116] The nano metal is nano silver particles with a particle size of 15 microns.
[0117] The line width of the strip protrusions is 0.2 mm.
[0118] The height of the strip-like protrusions is 6 microns.
[0119] refer to Figure 2 As shown, the strip-shaped protrusions are sinusoidal in shape and have an arched cross section.
[0120] The preparation method of the aluminum-plastic film is as follows: nano-metal and nylon particles are co-molded to obtain a composite nylon layer, and then a polypropylene film, an aluminum foil and the composite nylon layer are compounded.
[0121] In the composite nylon layer, the content of the nano silver particles is 1wt%.
[0122] The process parameters of co-molding include:
[0123] The temperature of the melt nano-metal particles and nylon is 240℃~260℃;
[0124] The injection pressure is between 50-150MPa;
[0125] The pressure maintaining time is 5s to 30s, and the cooling time is 10s to 60s.
[0126] Furthermore, a lithium-ion battery is prepared using the aluminum-plastic film prepared above, including a battery cell and an aluminum-plastic film wrapping the battery cell, wherein the battery cell includes a positive electrode sheet, a separator, a negative electrode sheet and the aluminum-plastic film.
[0127] (1) Preparation of positive electrode sheet
[0128] The positive electrode material lithium cobalt oxide, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system at a mass ratio of 97.9:1.3:0.8, and then coated on an aluminum foil, and then dried, rolled, and slit to obtain a positive electrode sheet.
[0129] (2) Preparation of negative electrode sheet
[0130] The negative electrode material (blended with 10% silicon carbon), conductive agent acetylene black, conductive agent single-arm carbon nanotube (SWCNT), binder styrene-butadiene rubber (SBR), lithiated polyacrylic acid (PAALI), and thickener sodium carboxymethyl cellulose (CMC) are fully stirred and mixed in a deionized water solvent system in a mass ratio of 96:0.5:0.05:1:1.95:0.5, and then coated on a copper foil, and then dried, rolled, and slit to obtain a negative electrode sheet.
[0131] (3) Preparation of isolation membrane
[0132] A polyethylene (PE) porous polymer film is used as the base layer of the isolation membrane, and an oil-based ceramic (PVDF and alumina ceramic) surface layer is provided on the surface of the base layer.
[0133] (4) Preparation of electrolyte
[0134] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP)) = 25:10:15:50 and a mass ratio of 8:92 was used as the electrolyte of the lithium battery.
[0135] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play a role of safety isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in the punched aluminum-plastic film, and the electrolyte is injected and packaged (because the nylon layer of the aluminum-plastic film is doped with metal, the polypropylene film is melted and packaged during packaging, which has no effect on the packaging), to obtain a lithium battery.
[0136] In Example 1, the particle size of the nano-silver particles is 35 nanometers, the amount added to the composite nylon layer is 1 wt%, and the shrinkage rate of the used diaphragm is 0.9%.
[0137] Example 2
[0138] The difference from Example 1 is that the particle size of the nano silver particles is 55 nanometers.
[0139] Example 3
[0140] The difference from Example 1 is that the particle size of the nano silver particles is 75 nanometers.
[0141] Example 4
[0142] The difference from Example 1 is that the content of the nano silver particles in the composite nylon layer is 3 wt %.
[0143] Example 5
[0144] The difference from Example 1 is that the particle size of the nano silver particles is 55 nanometers. The content of the nano silver particles in the composite nylon layer is 3 wt%.
[0145] Example 6
[0146] The difference from Example 1 is that the particle size of the nano silver particles is 75 nanometers. The content of the nano silver particles in the composite nylon layer is 3 wt%.
[0147] Example 7
[0148] The difference from Example 1 is that the content of the nano silver particles in the composite nylon layer is 5 wt %.
[0149] Example 8
[0150] The difference from Example 1 is that the particle size of the nano silver particles is 55 nanometers. The content of the nano silver particles in the composite nylon layer is 5 wt%.
[0151] Example 9
[0152] The difference from Example 1 is that the particle size of the nano silver particles is 75 nanometers. The content of the nano silver particles in the composite nylon layer is 5 wt%.
[0153] Example 10
[0154] The difference from Example 1 is that the nano metal is nano copper particles.
[0155] Embodiment 11
[0156] The difference from Example 1 is that the nano metal is nano copper particles, the particle size of the nano copper particles is 55 nanometers, and the content of the nano copper particles in the composite nylon layer is 1 wt%.
[0157] Example 12
[0158] The difference from Example 1 is that the nano metal is nano copper particles, the particle size of the nano copper particles is 75 nanometers, and the content of the nano copper particles in the composite nylon layer is 1 wt%.
[0159] Example 13
[0160] The difference from Example 1 is that the nano metal is nano copper particles, and the content of nano silver particles in the composite nylon layer is 3 wt %.
[0161] Embodiment 14
[0162] The difference from Example 1 is that the nano metal is nano copper particles, the particle size of the nano copper particles is 55 nanometers, and the content of the nano copper particles in the composite nylon layer is 3 wt%.
[0163] Embodiment 15
[0164] The difference from Example 1 is that the nano metal is nano copper particles, the particle size of the nano copper particles is 75 nanometers, and the content of the nano copper particles in the composite nylon layer is 3 wt%.
[0165] Example 16
[0166] The difference from Example 1 is that the nano metal is nano copper particles, and the content of the nano copper particles in the composite nylon layer is 5 wt %.
[0167] Embodiment 17
[0168] The difference from Example 1 is that the nano metal is nano copper particles, the particle size of the nano copper particles is 55 nanometers, and the content of the nano copper particles in the composite nylon layer is 5wt%.
[0169] Embodiment 18
[0170] The difference from Example 1 is that the nano metal is nano copper particles, the particle size of the nano copper particles is 75 nanometers, and the content of the nano copper particles in the composite nylon layer is 5wt%.
[0171] Embodiment 19
[0172] The difference from Example 1 is that the particle size of the nano silver particles is 55 nanometers. Figure 3 As shown, the strip-shaped protrusions are straight lines parallel to each other, and the spacing between the strip-shaped protrusions is 1 mm.
[0173] Embodiment 20
[0174] The difference from Example 1 is that the shrinkage rate of the diaphragm used is 1.45%.
[0175] Embodiment 21
[0176] The difference from Example 1 is that the particle size of the nano-silver particles is 55 nanometers, the shrinkage rate of the used diaphragm is 4.5%, and the content of the nano-silver particles in the composite nylon layer is 5wt%.
[0177] Comparative Example 1
[0178] The difference from Example 1 is that no nano metal is added.
[0179] Comparative Example 2
[0180] The difference from Example 1 is that no nano-metal is added, and the strip-shaped protrusions are straight lines parallel to each other.
[0181] Comparative Example 3
[0182] The difference from Example 1 is that no nano metal is added and the shrinkage rate of the diaphragm used is 1.45%.
[0183] Comparative Example 4
[0184] The difference from Example 1 is that no nano metal is added and the shrinkage rate of the diaphragm used is 4.5%.
[0185] Comparative Example 5
[0186] The difference from Example 1 is that the shrinkage rate of the diaphragm used is 4.5%.
[0187] Comparative Example 6
[0188] The difference from Example 1 is that the shrinkage rate of the used diaphragm is 0.5%, and the content of the nano silver particles in the composite nylon layer is 5 wt%.
[0189] The design parameters of the embodiments and comparative examples are shown in Table 1.
[0190] Table 1
[0191]
[0192]
[0193] Safety performance test
[0194] The batteries prepared in Examples 1 to 21 and Comparative Examples 1 to 6 were subjected to a lithium ion battery thermal abuse performance test.
[0195] Place the lithium-ion batteries in a 25℃ constant temperature chamber and let them stand for 30 minutes to allow the lithium-ion batteries to reach a constant temperature. Charge the lithium-ion batteries that have reached a constant temperature at a constant current of 0.5C to a voltage of 4.53V, then charge them at a constant voltage of 4.53V to a current of 0.05C, leave them for 60 minutes, and put the cells in an X℃ (X=124,126,128,130,132,134,136,138,140) oven. The oven temperature is raised to X℃ at a rate of 5±2℃ / min and kept for 30 minutes before stopping. During the process, monitor the cell surface temperature, ambient temperature and voltage. Specific test data are shown in Table 2.
[0196] Table 2
[0197]
[0198]
[0199] It can be seen from Table 2 that the temperature of the battery in the example is significantly higher than that of the comparative example, especially the battery in Examples 8 and 9 can still work stably at 140° C. This shows that the addition of nanometal and the use of a specific corrugation shape (such as a sine wave) effectively improve the thermal stability of the battery.
[0200] The nanosilver embodiments generally performed better than nanocopper, especially at higher mass fractions (such as 3% and 5%), the battery was able to pass the test at a higher temperature. For example, in Examples 8 and 9, nanosilver passed the test at 140°C at a mass fraction of 5%, while the temperature of nanocopper was slightly lower under the same conditions.
[0201] The effect of the particle size of the nanometal on the performance is also obvious. A larger particle size (such as 75 nanometers) is generally associated with higher thermal stability, such as Examples 3, 6, 9, 12, 15, and 18 showing a higher passing temperature.
[0202] In terms of the influence of the corrugation shape, the embodiments with a sine wave design are generally better than the embodiments with a straight corrugation shape (such as Embodiment 2 and Embodiment 19, Comparative Example 1 and Comparative Example 2). This indicates that the sine wave shape may have a better effect on heat dissipation.
[0203] Comparative Examples 1 and 2 performed the worst in the test, failing at 126° C. and 124° C., respectively, which are significantly lower than most of the examples, indicating the effectiveness of doping nanometals and design optimization (such as corrugated shape) in improving thermal stability.
[0204] Compared with Comparative Example 3, after the 1.45% high-yield diaphragm is doped with metal, the hot box still increases by 2°C.
[0205] Compared with Comparative Example 4, after the 4.5% high-yield diaphragm is doped with metal, the hot box still increases by 6°C.
[0206] Comparing Comparative Example 1 and Comparative Example 2, it can be seen that the heat box performance of the sine wave is better than that of the straight line.
[0207] Comparing Comparative Column 5 with Implementation Column 21, it can be seen that when Y / Z is not within the range, the performance of the hot box deteriorates.
[0208] Comparing Comparative Column 6 with Implementation Column 7, it can be seen that when Y / Z is not within the range, the hot box performance is better, but the cost is higher due to the use of a lower shrinkage diaphragm.
[0209] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A lithium ion battery, characterized in that: The invention comprises a battery cell and an aluminum-plastic film wrapping the battery cell, wherein the battery cell comprises a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, the shrinkage rate of the separator is Y%, the aluminum-plastic film comprises a polypropylene film, an aluminum foil and a composite nylon layer arranged in sequence, nano-metals are distributed in the composite nylon layer, the particle size of the nano-metals is 35nm to 75nm, and the addition amount of the nano-metals in the composite nylon layer is Zwt%, and the relationship between Y and Z satisfies 0.18≤Y / Z≤1.
45.
2. The lithium-ion battery according to claim 1, characterized in that The isolation membrane includes a base layer and a surface layer which are arranged in sequence; and / or, the material of the base layer includes PP or PE; and / or, the material of the surface layer includes PVDF and alumina ceramics.
3. The lithium-ion battery according to claim 1, characterized in that The outer surface of the composite nylon layer is provided with a plurality of strip-shaped protrusions; and / or the line width of the strip-shaped protrusions is 0.1 mm to 0.3 mm; and / or the height of the strip-shaped protrusions is 4 microns to 8 microns.
4. The lithium-ion battery according to claim 3, characterized in that: The strip-shaped protrusions are parallel to each other; and / or the spacing between the strip-shaped protrusions is 0.5 mm to 2 mm.
5. The lithium-ion battery according to claim 3, characterized in that: The strip-shaped protrusions are in a sinusoidal waveform; and / or the cross-section of the strip-shaped protrusions includes at least one of an arch, a triangle and a rectangle.
6. The lithium ion battery according to any one of claims 1 to 5, characterized in that The thickness of the polypropylene film is 30 microns to 80 microns; and / or the thickness of the aluminum foil is 20 microns to 40 microns; and / or the thickness of the composite nylon layer is 20 microns to 40 microns.
7. The lithium ion battery according to any one of claims 1 to 5, characterized in that A polyurethane adhesive layer is provided between the polypropylene film and the aluminum foil; and / or the thickness of the polyurethane adhesive layer is 1 micron to 3 microns.
8. The lithium ion battery according to any one of claims 1 to 5, characterized in that: A polyethylene naphthalate adhesive layer is provided between the aluminum foil and the composite nylon layer; and / or the polyethylene naphthalate adhesive layer has a thickness of 1 micron to 3 microns.
9. The lithium ion battery according to any one of claims 1 to 5, characterized in that: The nanometal includes nanosilver or nanocopper; and / or, the morphology of the nanometal includes nanosheets or nanoparticles.
10. The lithium ion battery according to any one of claims 1 to 5, characterized in that: The preparation method of the aluminum-plastic film comprises the steps of co-molding the nano-metal and nylon particles to obtain a composite nylon layer, and then compounding the polypropylene film, the aluminum foil and the composite nylon layer.
Citation Information
Patent Citations
Packaging material used for aluminum plastic film of lithium battery
CN107425147A
Aluminum plastic film and soft package battery
CN116417718A
Battery-packaging material, method for manufacturing the same, and battery
JP2019029300A
Sports arena
KR102122826B1
Packaging material for power storage device
US20180102514A1
Cited By
Separator, and electrochemical device and electronic device including same
CN121149598A